EDUKASI PHBS (PERILAKU HIDUP BERSIH DAN SEHAT) DAN PENYALURAN AIR BERSIH BAGI MASYARAKAT DESA TEMON GROBOGAN - Yuwanti; Anita Lufianti; Fitriani; Rahmawati; Yesita Ragil K; Christina Nur Widayati; Mika Agustina (LPPM AN Nuur, 2023)
Background: Clean and healthy living behavior is a collection of behaviors that are practiced on the basis of awareness as a result of accepted learning and make individuals, families, groups or communities able to help themselves. Behavior in society can be influenced by various things, including knowledge and attitudes. Purpose: this community service aims to provide PHBS (Clean and Healthy Living Behavior) education and Water Distribution for the people of Temon Grobogan village. Method: This community service uses lecture and discussion methods Results: The results of this community service are known that there is an increase in public knowledge about PHBS before and after education. Conclusion: PHBS education (clean and healthy living behavior) can increase public knowledge.